The clinical effectiveness of fine needle aspiration biopsy in patients with palpable breast lesions seen at the University College Hospital, Ibadan, Nigeria: A 10-year retrospective study - Ukah, Cornelius O (Medknow Publications Pvt Ltd, 2011)
BACKGROUND: Although open surgical biopsy is the ‘gold standard’ for diagnosis of palpable breast lesions, in recent years two types of minimally invasive breast biopsy techniques, core needle biopsy and fine needle aspiration biopsy (FNAB), have become established for the diagnostic evaluation of palpable breast lesions. AIMS: This study was undertaken to evaluate the clinical effectiveness of FNAB as a first line diagnostic procedure in the management of patients with breast lumps in University College Hospital (UCH), Ibadan, using the suggested thresholds for cytology performance as recommended by the United Kingdom National Health Services Breast Screening Programme (NHSBSP). SETTINGS AND DESIGN: A 10-year retrospective cohort study carried out in the Pathology Department of UCH. MATERIALS AND METHODS: All FNAB and histologically diagnosed cases of breast lesions in the pathology department between January 1996 and December 2005 were reviewed. The cytological diagnoses were then categorized into one of five diagnostic categories in accordance with the recommendations of the NHSBSP. RESULTS: The positive predictive value for malignancy was 99.3% with a complete sensitivity of 97.7% and specificity (full) of 94.2%. CONCLUSIONS: The high quality assurance measures obtained in this study affirms FNAB as a clinically effective diagnostic procedure for breast lesions.